Underutilization of GIS in health research in Pakistan: a literature review of Pakistani medline indexed journals - Ali Shaikh, Masood; Syed Muhammad Mubeen (Journal of the Pakistan Medical Association, 2025)
Understanding the spatial dimension of place, alongside time and personal characteristics, is essential in epidemiology. The current narrative review was planned to analyse articles from all three Medline-indexed general medical journals in Pakistan that reported on the use of Geographic Information System or the Global Positioning System. From 2011 till October 2024, a total of 20 studies were published; 18(90%) of them in the Journal of Pakistan Medical Association, including the first article in July 2011. Most studies focused on health risk assessment 12(60%), while 3(1.5%) examined health disparities and 2(1%) analysed spatial distribution and hospital accessibility. Geographic Information System facilitates spatial visualisation and analysis of health data, enabling a more nuanced understanding of disease patterns, hotspots and trends. This spatial intelligence is important for Pakistan, where geographical diversity, population density and socioeconomic disparities create complex health challenges. Key Words: Geographic information systems, Spatial, Pakistan.